Penerapan Media Pendidikan Kesehatan Terintegrasi Di Pos Pelayanan Terpadu (Posyandu) Madya Dalam Meningkatkan Cakupan Pelayanan: Application of Integrated Health Education Media in Madya Integrated Service Posts (Posyandu) in Increasing Service Coverage - Kayubi, Kayubi; Priyanto, Priyanto; Indra Ruswadi (BADAN PENERBIT STIEPARI PRESS, 2021)
The role of the posyandu in the community is very large, so it must be supported by the quality of human resources (HR) in the posyandu, in this case the posyandu cadres. The purpose of community service is to implement integrated health education media in intermediate integrated service posts (posyandu) in increasing service coverage. The implementation method is carried out by planning, implementing, monitoring and evaluating. This community service activity was focused on Kongsijaya Village, Widasari District, Indramayu Regency from 5 - 9 October 2020 with the subject of mentoring as many as 42 people. The results of the activity were the implementation of integrated health education media by posyandu cadres both at the posyandu and outside the posyandu. Conclusion: Integrated Health Education Media has been implemented well, Recommendation: related parties such as the Chair of the Village Posyandu Working Group and also the regional supervisor from Health should periodically and continuously provide guidance related to the use of this integrated Health Education media.